Simulasi Komunikasi Data Dengan Menggunakan Model Referensi OSI Pada Cisco Packet Tracer - Yunita Yunita; Iqbal Maulana; Agus Gilang Hermawan; Gelen Veranda Deanda; Muhammad Yusuf Habibi; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The use of Cisco Packet Tracer software in simulating computer networks is related to data communications. The steps explained include creating a network topology by selecting the end device, determining the IP address as the device identity, configuring the HTTP service including settings for the web server and PC, checking the connection via a web browser and carrying out live simulations. thoroughly using PDU samples. Then the simulation can be said to be successful if the sample PDU shows a tick on the PC device and the simulation display on the panel matches the settings in the sample PDU that have been determined, namely from the web server to the PC or from the PC to the web server. The entire explanation can provide practical guidance in using Cisco Packet Tracer software to simulate computer networks, namely by focusing on data communications and HTTP service configuration.